Mantle conductivity structure beneath eastern China using 3-D geomagnetic depth sounding - Ma, Xinpeng; Li, Jingru; Xu, Kaijun (Frontiers in Earth Science, 2025)
The distribution of water in the mantle plays a critical role in deep earth dynamic processes, including plate subduction, earthquake generation, and magmatic activity. Seismic tomography studies have consistently shown that the subducted Pacific plate beneath eastern China stagnates within the mantle transition zone. The release of water from the slab can substantially modify the surrounding electrical properties, producing pronounced high-conductivity anomalies. Resolving the regional conductivity structure is therefore essential for constraining the geometry and dehydration state of the stagnant slab, as well as for improving our understanding of the strong seismicity and widespread Cenozoic volcanism in eastern China. Conventional magnetotelluric (MT) surveys are constrained by their frequency range and cannot resolve deep structures on thousand-kilometer scales. Geomagnetic depth sounding (GDS), which utilizes ultra-long-period signals (>100 days), can image the mantle down to ∼1,600 km, making it a powerful approach for investigating mantle water content and partial melting. Here, we compile long-term geomagnetic records from an array covering eastern China and apply a three-dimensional unstructured finite-element GDS modeling and inversion scheme. The inversion employs a limited-memory quasi-Newton optimization strategy to improve computational efficiency and model stability. The resulting electrical resistivity model delineates the mantle transition zone and lower mantle beneath eastern China, clearly imaging the stagnant Pacific slab and indicating possible dehydration and melting processes. These findings offer new constraints and insights into the structure and dynamics of the deep earth.